1992
DOI: 10.1116/1.577869
|View full text |Cite
|
Sign up to set email alerts
|

Energy-resolved angular distributions of O+ ions at the radio-frequency-powered electrode in reactive ion etching

Abstract: Mass-selected distributions of bombardment energies of O+ ions at the powered electrode of a reactive ion etcher are investigated under angles between ±10° with respect to the electrode normal. The energy distributions consist of split high-energy peaks and continuous intensities between 50 eV and the maximal energy defined by the potential drop across the sheath. Ions found in the bimodal split high-energy peaks show angular distributions with widths between 2° and 6° [full width at half-maximum (FWHM)]. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The ion mean free path can be determined from equation (7), in which k B denotes the Boltzmann constant, T g the gas temperature, p the pressure and σ the ion-neutral charge exchange collision cross section:…”
Section: Evaluation Of Current-voltage Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ion mean free path can be determined from equation (7), in which k B denotes the Boltzmann constant, T g the gas temperature, p the pressure and σ the ion-neutral charge exchange collision cross section:…”
Section: Evaluation Of Current-voltage Characteristicsmentioning
confidence: 99%
“…Several experimental and theoretical methods have been developed and applied to determine the ion flux and the ion energy distribution at the substrate, such as the use of ion mass/energy analyzers [7][8][9] or extensive modelling of plasma and sheath [10][11][12][13][14]. Among the experimental methods, retarding field analyzers (RFAs) have gained a lot of interest due to their ease of use and simple implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the measurement of ion kinetic-energy distributions (IEDs) in low pressure, rf discharges generated in parallel-plate reactors has been used to investigate: (1) ion bombardment of the grounded electrode in argon plasmas [510]; (2) the role of ions in discharges sustained in etching gases [1113]; (3) the angular distribution of ions striking the electrodes [14,15]; and (4) the effect of symmetric charge-transfer collisions on the shapes of IEDs [16]. Additional experiments have been performed to measure the energies of ions striking the surface of the powered electrode in capacitively coupled rf discharges [13,15, 1719].…”
Section: Introductionmentioning
confidence: 99%
“…Additional experiments have been performed to measure the energies of ions striking the surface of the powered electrode in capacitively coupled rf discharges [13,15, 1719]. …”
Section: Introductionmentioning
confidence: 99%
“…The development of floating [6][7][8][9][10] and radio frequencyfiltered [11] retarding field analyzers (RFAs) has delivered deep insight into the ion bombardment of sinusoidally biased electrodes. Some authors have reported on the use of ion mass/energy analyzers behind sinusoidally biased electrodes [6,12,13]. The observed ion energy distributions are typically bimodal and span a broad energy band.…”
Section: Introductionmentioning
confidence: 99%